Hubungan antara konsep takdir dengan post-traumatic stress disorder: Kajian dari perspektif psikospiritual Islam / Muhammad Hazim Mohd Azhar - Muhammad Hazim, Mohd Azhar (2018)
Post-Traumatic Stress Disorder also known as PTSD, is a mental disorder which involves mind, soul and spirit as well as creating gaps in social relations. Patient who suffered from PTSD should be addressed and tackled by all individual Muslims as a social responsibility. Islam as a comprehensive religion, deeply concerns on the aspects of mind and soul that both of them has been placed in the list of al-daruriyyat al-khams in order to strive for care and maintenance of al-‘Aql and al-Nafs. This study entitled Relation between Concept of Taqdir with Post-Traumatic Stress Disorder: A Study from Islamic Psychospiritual Perspective, trying to analyze relations between the religious which a focus on the concept of fate as psychospiritual support to the treatment of PTSD. This qualitative study applied the conceptual documentation as a method of data collection and content analysis as a method of data analysis. This study shows the feels and appreciation based on dhauqiyyah which is a result of the construction of knowledge and understanding with the ‘aqliyyah based help the PTSD treatment through the process of spiritual methods individually. Accordingly, through this study, suggests the improvement of existing treatment with an emphasis on the aspects of religious spirituality through al-Qada’ and al-Qadr.